Pengaruh Penguasaan Kosakata, Sintaksis, dan Minat Baca terhadap Kemampuan Memahami Bacaan Teks Berbahasa Inggris - Arifin, Muhammad Zainal (Jurnal Studi Agama dan Masyarakat, 2010)
This study aims to investigate the influence of the mastery of vocabulary, syntax, and reading interest towards the comprehension of English reading texts. This research is an ex-post facto, involving three independent variables and one dependent variable. The mastery of vocabulary is the first independent variable (X1), syntax is the second independent variable (X2), and reading interest is the third independent variable (X3). The comprehension of English reading texts is the dependent variable (Y). This research was conducted at State College of Islamic Studies (STAIN) Palangka Raya in academic year 2008/2009. Among 249 students, only 151 were used as sample, selected using the proportional cluster random sampling. The research instruments used tests and questionnaires. The data are analyzed using multiple regression statistics analysis technique and partial correlation.Â Â Â Â Â Â Â Â Â Â Â  The result of descriptive analysis indicates that the mastery of vocabulary is in very good category (70.20%), syntax is in good category (57.61%), reading interest is in good category (67.54%), and the comprehension of English reading texts is in good category (52.32%). The result of multiple regression indicates that the mastery of vocabulary, syntax, and reading interest in aggregate influences the comprehension of English reading texts (F = 13.121 sig. Ï < 0.05). As many as 64.1% variance of the comprehension of English reading texts is determined by the mastery of vocabulary, syntax, and reading interest. The result of the partial correlation indicates that the mastery of vocabulary influences the comprehension of English reading texts (r = 0.504 sig. Ï < 0.05) with a contribution as many as 22.6%. Syntax influences the comprehension of English reading texts (r = 0.619 sig. Ï < 0.05) with a contribution as many as 25.6%. Reading interest influences the comprehension of English reading texts (r = 0.242 sig. Ï < 0.05) with a contribution as many as 16.9%.